2021
DOI: 10.3390/ma14216537
|View full text |Cite
|
Sign up to set email alerts
|

Calculation Based on the Formation of Mg2Si and Its Effect on the Microstructure and Properties of Al–Si Alloys

Abstract: In order to investigate the effect of Mg2Si formation on the microstructure and properties of an Al−Si alloy, the critical point of a hypereutectic Al−17Si−4Cu−Mg alloy was calculated by Pandat software. The calculation results of the equilibrium phase diagram show that the critical point for Mg2Si phase formation for the alloy was obtained when the Mg content was 2.2%. The contents of 0.5 wt.% Mg and 2.5 wt.% Mg were selected as the research object. The content of Mg increased from 0.5 wt.% to 2.5 wt.%, the e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 30 publications
0
5
0
Order By: Relevance
“…FSW can improve mechanical properties such as fracture toughness, fatigue, and ductility (Hao et al, 2021) .Looking at the fracture mode of four samples of cold reduced material highlighted in figure 4b shows that the material is more ductile as compared to as-received material and this justifies why there is less decrease in mechanical properties on it as compared to as-received FSW welded material. Some of the deviations that might have influence in the results of tensile tests are hooking defects which is one of the most common defects observed in FSW lap joints, which results in a decrease of mechanical properties in the weld when found in the load path (Gungor et al, 2014) to the material used in this study.…”
Section: Tensile Test Resultsmentioning
confidence: 96%
See 1 more Smart Citation
“…FSW can improve mechanical properties such as fracture toughness, fatigue, and ductility (Hao et al, 2021) .Looking at the fracture mode of four samples of cold reduced material highlighted in figure 4b shows that the material is more ductile as compared to as-received material and this justifies why there is less decrease in mechanical properties on it as compared to as-received FSW welded material. Some of the deviations that might have influence in the results of tensile tests are hooking defects which is one of the most common defects observed in FSW lap joints, which results in a decrease of mechanical properties in the weld when found in the load path (Gungor et al, 2014) to the material used in this study.…”
Section: Tensile Test Resultsmentioning
confidence: 96%
“…The second phases identified were Mg2Si shown on both cold rolled and as-received material WZ. Mg2Si has a low density (1.90 g/cm3), a high melting point (1087 ºC), a high hardness (4.5×10^9 N/m^2) , a high modulus of elasticity around (120 GPa) and a low thermal expansion coefficient (7.5×10^9) and will have a great influence on the mechanical properties of the material (Hao et al, 2021). Mg2Si phases identified on the welded zone of both samples are surrounded by α-Al (white spots), which contain silicon.…”
Section: Resultsmentioning
confidence: 99%
“…This was due to the nature of the analysis, which also analysed the background of the sample. The phases were determined on the basis of EDS analyses and previous reports [17,18,[20][21][22][23].…”
Section: Metallographymentioning
confidence: 99%
“…Another observation that can be made from Figure 5a is that the undercooling (TG-TN) associated with the development of the α-Al network is more explicit than those observed for the (Al-Si) and (Al-Al2Cu) eutectic reactions. The importance of the ∆Tα undercooling is that it defines the degree of the alloy grain refining [29,30]. It has been reported that the addition of a high percentage of Fe to die-cast alloys prevents the soldering of the casting with the steel die.…”
Section: Thermal Analysismentioning
confidence: 99%